2019
DOI: 10.1590/1678-9865201932e180170
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-processed food consumption and obesity in adolescents

Abstract: Objective To evaluate the relationship between ultra-processed food consumption and obesity indicators in adolescents. Methods Cross-sectional study with a convenience sample of 200 10- to 18-year-old adolescents from Campinas, São Paulo (SP). Usual dietary intake was determined through a semiquantitative food frequency questionnaire. Daily intake of each food was obtained from the intake frequency. Subsequently, foods were classified as raw and minimally processed, cooking ingredients or ultra-processed food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 24 publications
4
37
0
13
Order By: Relevance
“…Study types were ecological ( n = 3), cross-sectional ( n = 19), prospective cohort ( n = 19), case–control ( n = 1); and one randomised controlled trial (RCT). Studies were conducted in Brazil ( n = 16) [ 53 , 56 , 62 , 63 , 66 , 70 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ], France ( n = 8) [ 61 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ], Spain ( n = 6) [ 65 , 72 , 90 , 91 , 92 , 93 ], USA ( n = 4) [ 59 , 67 , 71 , 94 ], Canada ( n = 2) [ 57 , 68 ], UK ( n = 2) [ 55 , 60 ], and one each in Sweden [ 36 ], Lebanon [ 69 ] and Malaysia [ 64 ]. There was one study on 19 European countries [ 52 ], and one global study [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Study types were ecological ( n = 3), cross-sectional ( n = 19), prospective cohort ( n = 19), case–control ( n = 1); and one randomised controlled trial (RCT). Studies were conducted in Brazil ( n = 16) [ 53 , 56 , 62 , 63 , 66 , 70 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ], France ( n = 8) [ 61 , 83 , 84 , 85 , 86 , 87 , 88 , 89 ], Spain ( n = 6) [ 65 , 72 , 90 , 91 , 92 , 93 ], USA ( n = 4) [ 59 , 67 , 71 , 94 ], Canada ( n = 2) [ 57 , 68 ], UK ( n = 2) [ 55 , 60 ], and one each in Sweden [ 36 ], Lebanon [ 69 ] and Malaysia [ 64 ]. There was one study on 19 European countries [ 52 ], and one global study [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In children and adolescents (Brazil only) the proportion of total energy intake from UPF was reported as 41.8–43.4% at ages 3–4 years, 47.7–49.2% at ages 6–8 years [ 77 , 78 , 79 ] and 50.6% in adolescents [ 73 ]. One study reported 46.2% of adolescents consumed UPF weekly (median ≥ 3 times per week) [ 76 ], and another study reported frequency intakes varied from 9.9 (private schools) to 14.5 (public schools) times per day [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations